Integral means of certain class of analytic functions - Gao Chunyi (International Journal of Mathematics and Mathematical Sciences)
In this paper we discuss the following class of functions Sλ(α,β)={f(z):|f(z)g(z)−1|<β|λf(z)g(z)+1|,z∈D}  where  0≤λ≤1,0<β≤1,0≤α<1, and f(z)=z+∑n=2∞anzn is analytic in D={z:|z|<1}, g(z) is a starlike function of order α. A subordination about this class is obtained, the integral means of functions in Sλ(α,β) and some extremal properties are studied.